2014 Stopwatch Interlaborator y Comparison - Fallas-Cordero, Oscar (2015)
Stopwatches and timers are used for numerous applications and are among the most common devices calibrated metrology laboratories. Timer´s calibrations are typically carry out by secondary laboratories, as well as state or private laboratories. However, in small countries, the national metrology institute (NMI) often accepts timers for calibration with the national standard. This paper presents and describes the results of a timer comparison conducted in Costa Rica, from March 2014 until October 2014, by the Instituto Costarricense de Electricidad (ICE)- Laboratorio Metrológico de Variables Eléctricas (LMVE) as a designated NMI in Costa Rica for Electricity, Magnetism, Time and Frequency. The comparison involved six participating laboratories and a standard stopwatch traveler.